2018
DOI: 10.3892/etm.2018.6820
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of microRNA‑455‑5p on biological functions of esophageal squamous cell carcinoma Eca109 cells via Rab31

Abstract: The aim of the present study was to examine microRNA (miRNA or miR)-455-5p expression in esophageal squamous cell carcinoma (ESCC) at the tissue and cellular levels in order to elucidate its biological roles. A total of 60 patients with ESCC were enrolled in the present study and reverse transcription-quantitative polymerase chain reaction was used to measure the expression of miR-455-5p. ESCC Eca109 cells were transfected with miR-NC, miR-455-5p mimics or inhibitor and a Cell Counting Kit-8 assay was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Many such studies have been published so far, which reveal miRNAs as tumor suppressors or oncogenes (Table 1). For example, miR-146a, miR-133b, miR-106b-3p, miR-219-5p, miR-206, miR-384, miR-455-5p, miR-128, miR-145-3p/5p, miR-10b-3p, miR-874-3p, miR-10a, miR-365, miR-301a, miR-6775-3p, miR-139-5p, miR-516b, miR-449a-5p, miR-125b, miR-433-3p, miR-370, miR-133b, miR-30a-3p/5p, miR-34a, miR-196a, and miR-125b-5p have been shown to act as tumor suppressors by inhibiting ESCC cell proliferation, promoting apoptosis by directly targeting oncogenes, or antagonizing pro-cancer signaling pathways [29,33,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][60][61][62][63]110,133]. In contrast, pro-oncogenes such as miR-141, miR-21, miR-10b-3p, miR-424, miR-675-3p, miR-543, miR-135, miR-23b-3p, miR-502, miR-21-5p, and miR-548k have been reported to play contrasting roles in promoting cell proliferation or suppressing apoptosis in ESCC [47,[64][65][66][67][68][69][70][71][72][73].…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%
See 1 more Smart Citation
“…Many such studies have been published so far, which reveal miRNAs as tumor suppressors or oncogenes (Table 1). For example, miR-146a, miR-133b, miR-106b-3p, miR-219-5p, miR-206, miR-384, miR-455-5p, miR-128, miR-145-3p/5p, miR-10b-3p, miR-874-3p, miR-10a, miR-365, miR-301a, miR-6775-3p, miR-139-5p, miR-516b, miR-449a-5p, miR-125b, miR-433-3p, miR-370, miR-133b, miR-30a-3p/5p, miR-34a, miR-196a, and miR-125b-5p have been shown to act as tumor suppressors by inhibiting ESCC cell proliferation, promoting apoptosis by directly targeting oncogenes, or antagonizing pro-cancer signaling pathways [29,33,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][60][61][62][63]110,133]. In contrast, pro-oncogenes such as miR-141, miR-21, miR-10b-3p, miR-424, miR-675-3p, miR-543, miR-135, miR-23b-3p, miR-502, miR-21-5p, and miR-548k have been reported to play contrasting roles in promoting cell proliferation or suppressing apoptosis in ESCC [47,[64][65][66][67][68][69][70][71][72][73].…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%
“…At present, various miRNAs have been found to regulate EMT or tumor metastasis of ESCC. It has been reported that miR-106b-3p, miR-455-5p, and miR-128 function as tumor suppressors, and have suppressed EMT or metastasis in ESCC [33,43,44]. While miRNAs, such as miR-543, miR-23b-3p, miR-25, and miR-99b/let-7e/miR-125a play oncogenic roles in promoting EMT or metastasis during ESCC progression [68,70,109,113].…”
Section: Non-coding Rnas and Emt And Metastasis In Esccmentioning
confidence: 99%
“…RAB31 expression has been confirmed in many colorectal cancer cell lines, which is consistent with clinical data that may indicate variations in morphology during the EMT process. The expression of RAB31 has been demonstrated to affect cell growth and motility in various cancer types such as esophageal squamous cell carcinoma, osteosarcoma and cervical cancer (Huang et al., 2022 ; Liu et al., 2018 ; Wu et al., 2020 ). Establishing a RAB31‐based model confirmed a correlation between the expression of E‐cadherin and mesenchymal‐related molecules (SNAI2, VIM and TWIST1) at the RNA and protein levels in colorectal cancer cells and RAB31 biological function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the factors mentioned on sixty tumor tissues were compared with the adjacent healthy tissue and it was reported that miR455-5p can be thought as a miR suppressive tumor and plays a significant role in esophageal SCC by typically suppressing the expression of Rab31. It is important to note that soft tissues of the human oral cavity and esophagus are covered everywhere by a stratifying squamous epithelium (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%